If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+9=7x+10
We move all terms to the left:
8x+9-(7x+10)=0
We get rid of parentheses
8x-7x-10+9=0
We add all the numbers together, and all the variables
x-1=0
We move all terms containing x to the left, all other terms to the right
x=1
| 9.5x+6.9=2.5 | | x/5+4×=1/2 | | 6(1-8k)=6 | | 92z+45=−292z+45=−2 | | y=18(2) | | 3w-1=4 | | 50-15x+x^2=0 | | 11x+9=10x+15 | | 1.0x=4.5 | | -2/3x+3=1/3x+11 | | 10x+3x+15=20x-7 | | 54x=12 | | 54•x=12 | | x+45=11 | | 6.4y-5.4y-3.1=-0.3 | | a/8=5/8 | | x=21+34 | | 56-10x=20=8x | | 1/5y=-6 | | 2n-1=9- | | 6x+34=20 | | (3x-3)(2x+3)=180° | | 7-8k=79 | | X×2x=575 | | -v-5=-1 | | 0.8+3.2=x | | 91m^2+m+-2=0 | | 105=-7(1-2x) | | 10-4k=-2 | | (-2/5x+3)-(1/5x+11)=0 | | -21=-5x-6=-11 | | 2-5x=52 |